(3ebGdI aj ESJNQGL SGYGJ eG Hjf WdhY GdaLQ hWdhY GdTeS cd jhe ef CjGe GdSfI HeOjfI bGjfs - (3CHh GdMSf Ydj Hf YHO Gddg Hf eMeO Hf HGTGP GdbGjfjs
(3ChdgG (B:s
(3bGd CHh GdMSf Ydi Hf YHO Gddg Hf eMeO Hf HGTGP GdbGjfi SFdJ ESJNQGL SGYGJ eG Hjf WdhY GdaLQ hWdhY GdTeS cd jhe ef CjGe GdSfI HeOjfI bGjf s
(3BNQgG (B:s
(3jfJgi HLOhd CReGf SGYGJ eG Hjf WdhY GdaLQ hWdhY GdTeS Ch ZQhHgG hZQhH GdTab s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3Gdadcs